SPEAK UP®: DEVELOPING INDONESIAN EFL LEARNERS’ VOCABULARY AND IMPROVING THEIR SPEAKING SKILLS - Ima Normalia Kusmayanti (English Review: Journal of English Education, 2025)
Research indicates that incorporating educational games can significantly enhance second or foreign language learning. This study examines the effectiveness of the board game Speak Up® in improving English vocabulary and speaking skills among Indonesian EFL learners. Over eight weeks, the research involved 30 high-beginner EFL learners, employing vocabulary tests, speaking tests, and a survey for data collection. The analysis utilized paired t-tests for the test results and descriptive analysis for the survey findings. The results demonstrated notable improvements in both vocabulary and speaking skills, with a t-value of -13.772 for vocabulary and a z-value of -4.816 for speaking, confirming that Speak Up® effectively enhanced learners' abilities. Additionally, a positive correlation was identified between vocabulary acquisition and speaking fluency, with an effect size of 0.85, indicating a substantial impact. Survey results reflected favorable perceptions of Speak Up®, with mean scores of 4.56 for effectiveness, 4.59 for usability, and 4.62 for satisfaction. Based on these findings, it is recommended that EFL teachers incorporate Speak Up® into their teaching strategies to improve vocabulary and speaking skills. Future research could investigate the long-term effects of Speak Up® on vocabulary retention and explore its benefits for improving speaking skills with a larger, more diverse sample, while also considering external factors that may influence vocabulary development and speaking skills.